RESIDU INSEKTISIDA SIDAZINON PADA KACANG PANJANG (VIGNA SINENSIS) YANG DIHASILKAN DI DESA TUNJUK SELATAN, KECAMATAN TABANAN, KABUPATEN TABANAN - I Gusti Ayu Lani Triani (Bumi Lestari Journal of Environment)
Research was conducted in long bean (Vigna sinensis) that has been produced inTabanan district, Tabanan Regency concerning the residue of Sidazinon insecticide. Theaims of this study are to : know dosage Sidazinon insecticide utilized by farmer inTabanan district and the level of the residue of Sidazinon insecticide found in long bean.The determination of the sample of the farmer of long bean was done inproportional and purposive sampling. The sample was taken in Tabanan district, inTabanan Regency. For the selection of village, search by 10 % from amount village exist,so five of the farmer of long bean were obtained in Tabanan district.The finding show that the residue of the Sidazinon insecticide in long beanproduced in Tabanan district in influenced by the use of dosage was 9,275 ml/ are. Theresidue of Sidazinon insecticide in long bean averagely produced in Tabanan district was0,03045 ppm.